Efektivitas Promosi Terhadap Peningkatan Penjualan di Maxx Cofee Benton Junction - lusiana maribet manurung; Diena Mutiara Lemy (HOSPITALITI DAN PARIWISATA, 2021)
Effectiveness Of Promotion To Increase Sales In Maxx Coffee Benton Junction. Maxx Coffee is one of the local coffee shops under Lippo Group Company. This business does promotion to increase its sales. The purpose of this research is to identify the promotion strategies and analyze their effectiveness by using advertising, sales promotion, publication personal selling, and merchendise. This internship report uses the qualitative approach. The methods are interviewing the chosen respondents the understand the problem of the research and observing the promotion and respondents’ response toward it. The result of this research shows that promotion strategies by advertising, sales promotion, publication personal selling, and merchandise are effective to increase the sales.